The usability of the brick dust and blast furnace slag in zeolite-based lime mortars in different curing environments. Issue 3 (1st February 2023) - Çavuş, Murat; Dayı, Mustafa; Dağcı, Yunus; Ulusu, Hayati
Abstract: In this study, air lime was substituted by three different pozzolanic materials, namely BFS and brick powder and zeolite in different proportions as individual or double. The produced pozzolanic lime mortars were cured in air and high relative humidity environments. Special attention was given to the mechanical and physical properties of mortars under different curing conditions. In addition to the curing effect, the effect of using different pozzolans was also investigated. As a result, it has been observed that high relative humidity cure improves the mechanical properties of pozzolan mortars but is not effective on their physical properties. It shows that there are significant differences in the mechanical properties of mortars with pozzolan, which are exposed to different curing conditions, especially at an early age. It shows that the mechanical properties of mortars with pozzolan, which are exposed to different curing conditions, especially at an early age, increase twice on average. The high relative humidity cure shows that the non-pozzolan air-lime mortars slow down the performance properties. Overall, conditions of high relative humidity can more quickly improve the performance characteristics of puzolan mortars. Graphical abstract: Image 1